Piloting the Power of the Post: The Impact of Parents' Social Media Use on Canadian Urban Middle Level Principals - Erika Nelson (Canadian Society for Studies in Education, 2023)
This study examines principals' perceptions of how their work is impacted by parents through their social media use. This research was borne of a pilot research project conducted as a first step toward doctoral candidacy. Although conducted on a smaller scale with limitations in both size and scope, the data and interpretations derived from the completion of this pilot provide solid insights into this phenomenon and establish a baseline for further research. The data was collected from an online survey and semi-structured interviews with five Canadian urban middle level principals. The data was analysed using the "Sort, Sift, Think, and Shift" method of qualitative data analysis honed by Maietta et al. (2021). The research emphasizes the concerns of school principals regarding parents' behaviour on social media platforms and their perceptions of how this behaviour affects their schedule, decision-making process, and overall role as principals. This paper focuses on how principals feel overall while also illustrating the value of conducting a pilot in doctoral research.